Antioxidant and Anticancer Activities of Wampee (Clausena lansium (Lour.) Skeels) Peel. (30th July 2009) - Prasad, K. Nagendra; Hao, Jing; Yi, Chun; Zhang, Dandan; Qiu, Shengxiang; Jiang, Yueming; Zhang, Mingwei; Chen, Feng
Abstract : Antioxidant activities of wampee peel extracts using five different solvents (ethanol, hexane, ethyl acetate, butanol and water) were determined by using in-vitro antioxidant models including total antioxidant capability, 1, 1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging activity, reducing power, and superoxide scavenging activity. Ethyl acetate fraction (EAF) exhibited the highest antioxidant activity compared to other fractions, even higher than synthetic antioxidant butylated hydroxyl toluene (BHT). In addition, the EAF exhibited strong anticancer activities against human gastric carcinoma (SGC-7901), human hepatocellular liver carcinoma (HepG-2) and human lung adenocarcinoma (A-549) cancer cell lines, higher than cisplatin, a conventional anticancer drug. The total phenolic content of wampee fraction was positively correlated with the antioxidant activity. This is the first report on the antioxidant and anticancer activities of the wampee peel extract. Thus, wampee peel can be used potentially as a readily accessible source of natural antioxidants and a possible pharmaceutical supplement.